2023
DOI: 10.1002/prp2.1071
|View full text |Cite
|
Sign up to set email alerts
|

The influence of SARS‐CoV‐2 infection on expression of drug‐metabolizing enzymes and transporters in a hACE2 murine model

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and the resulting Coronavirus disease 2019 emerged in late 2019 and is responsible for significant morbidity and mortality worldwide. A hallmark of severe COVID‐19 is exaggerated systemic inflammation, regarded as a “cytokine storm,” which contributes to the damage of various organs, primarily the lungs. The inflammation associated with some viral illnesses is known to alter the expression of drug‐metabolizing enzymes and transporters. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(82 reference statements)
0
0
0
Order By: Relevance
“…In this context, it has been documented that the increased proinflammatory cytokines induced by COVID-19 impact drug metabolism as they interfere with the regulation of CYP enzymes and drug transporter expression [68,71,72]. In humans, it has been observed that inflammation caused by COVID-19 reduces CYP3A activity, which, in turn, affects the metabolism of midazolam.…”
Section: Inflammation As a Results Of Infection Modifies Drug Responsementioning
confidence: 99%
“…In this context, it has been documented that the increased proinflammatory cytokines induced by COVID-19 impact drug metabolism as they interfere with the regulation of CYP enzymes and drug transporter expression [68,71,72]. In humans, it has been observed that inflammation caused by COVID-19 reduces CYP3A activity, which, in turn, affects the metabolism of midazolam.…”
Section: Inflammation As a Results Of Infection Modifies Drug Responsementioning
confidence: 99%